Effects of Ethanol on Hematological, Histopathological, and Antioxidant on Indomethacin-induced Heat-stressed Rats - Adeleye, G. S. (International Journal of Pharmaceutical & Biological Archive, 2023)
The non-steroidal anti-inflammatory medicine indomethacin causes pathogenesis that involves reactive oxygen species and lipid peroxidation. This study examined how ethanol and indomethacin affected heat-stressed rats’ hematological, histopathological, and antioxidant functions. Three groups of 18 male albino rats were created. Group A acted as the standard control group and received saline as usual for 15 days. Group B was given 0.2 mL of ethanol orally each day. In group C, indomethacin 10 mg/kg/day was administered orally once daily. Rats given ethanol and indomethacin had significantly lower levels of red blood cells, packed cell volume, and hemoglobin compared to the control group. White blood cell (WBC), lymphocyte (LYM), and neutrophil (NEUT) levels were significantly altered by the addition of ethanol and indomethacin, with indomethacin administration significantly increasing WBC and NEUT in comparison to ethanol administration. Compared to the stress control group, the levels of malondialdehyde and superoxide dismutase were significantly elevated and decreased, respectively, in the rats supplemented with ethanol and indomethacin. In addition, rats given ethanol and indomethacin showed significantly reduced catalase, glutathione, and glutathione peroxidase activities. The stomachs of rats given indomethacin and ethanol treatment underwent histological analysis, which revealed varying degrees of architectural deformities. These results imply that supplementation with ethanol and indomethacin may harm rats under heat stress.